Immuno-histochemical, pathological, enzyme linked immunosorbent assay and polymerase chain reaction analysis of experimental Ornithobacterium rhinotracheale infection in quails (Coturnix coturnix japonica) - Eroksuz, H; Ozbey, G; Cevik, A; Tarakci, BG; Turgut-Balik, D (Ecole Nationale Veterinaire Toulouse, 2006)
The aims of this study were to analyse the direct pathogene role of Ornithobacterium rhinotracheale (ORT) in the respiratory tract of birds and to identify a set of techniques useful for infection diagnosis. For that, a total of 30 male 10 week old quails were infected via aerosol route by ORT strain B3263/91 (serotype A) and 30 other quails were used as negative controls. On the 1(st), 3(rd) and the 6(th) weeks post infection, 10 birds of each group were slaughtered, then lung and trachea were examined by bacteriological (cultures and PCR) and immuno-histochemical methods. In addition, the occurrence of serum anti-ORT antibodies was investigated by an enzyme-linked immunosorbent assay (ELISA). The experimental ORT inoculation have induced macroscopic lesions characterised by mild pulmonary and tracheal hyperemia and pleural thickening on weeks 3 and 6. Microscopically. patchy necrosis and desquamation of tracheal epithelium associated with subepithelial hemorrhage and subserosal oedema were observed and the interalveolar septa and pleural thickening was due to inflammatory infiltration. ORT was evidenced by immuno-chemistry in temporary microscopic lung lesions at the 3(rd) and 6(th) weeks. whereas ORT was isolated and identified from trachea of four quails (10%) and from lung of only one quail (2.5%). A seroconversion was observed in all infected birds mainly during the 1(st) week (80%) and also during the 3(rd) week (20%). but the serological response was transient since antibodies were no more detected in the sera of infected quails on the 6th week. In non infected quails. no macroscopic and microscopic damage was observed, no germ could be found by culture or PCR and birds remained seronegative during all the experiment. In conclusion, among the diagnostic methods used. ELISA test was the more sensitive and for the fisrt time in Turkey. the respiratory syndrome associated with ORT was experimentally induced in quails.
Keywords: Ornithobacterium rhinotracheale; culture; ELISA; immuno-histochemistry; PCR